Living arrangements and cognitive abilities of community‐dwelling older adults in Singapore - Roystonn, Kumarasan; Abdin, Edimansyah; Shahwan, Shazana; Zhang, Yunjue; Sambasivam, Rajeswari; Vaingankar, Janhavi Ajit; Mahendran, Rathi; Chua, Hong Choon; Chong, Siow Ann; Subramaniam, Mythily (Psychogeriatrics, 2020)
Aim Dementia is a growing public health concern. It is necessary to focus on factors that may help preserve cognitive function in late life. Limited research has examined how living arrangements are associated with cognitive function in older adults. This study aims to further our understanding of this association in community‐dwelling older adults in a multi‐ethnic Asian population. Methods Data were obtained from a cross‐sectional population survey of 2548 adults aged 60 and older with standardized instruments. Living arrangements were classified as living with adult children and grandchildren, living with adult children only, living with a spouse/partner only, living alone, living with other relatives, and living with non‐relatives. Results Cognitive function was significantly predicted by living arrangements among community‐dwelling older adults. Multivariate linear regression analyses revealed that older adults in multigenerational family households had significantly poorer cognitive function than those living with a spouse/partner (β = 0.54, P < 0.02) and those living with non‐relatives (β = 1.08, P < 0.02). This association was independent of the influence of age, gender, ethnicity, education, employment status, marital status, depression, disability, chronic health conditions, and self‐reported health. Conclusion Older adults living in multigenerational households seem to be disadvantaged in their cognitive function. However, we cannot conclude this based on the evidence because of the cross‐sectional nature of the data. Further research is needed to reasonably determine the relationship between living arrangements and cognitive function. Regardless, these findings add to the growing understanding of the complex relationship between living arrangements and cognition in older adults and could provide a basis to design effective strategies to delay cognitive decline in community‐dwelling older adults.